A finite element model for unbonded flexible pipe under combined axisymmetric and bending loads - Lu, Hailong; Vaz, Murilo Augusto; Caire, Marcelo (Marine structures, 2020)
Flexible pipes are key equipment for offshore oil and gas production systems, conveying fluids between the platform and subsea wells. The structural arrangement of unbonded flexible pipes is quite complex, encompassing several layers with polymeric, metallic and textile materials. Different topologies and a large amount of intricate nonlinear contact interactions between and within their components, especially because of the relative stick-slip mechanism during bending, makes numerical analysis challenging. This paper presents an alternative three-dimensional nonlinear finite element model that describes the response of flexible pipes subjected to combined axisymmetric and bending loads. To simulate the response of a flexible pipe under axial tension or compression combined with uniform curvature, an equivalent thermal loading is employed on the external sheath, which is modelled as an orthotropic thermal expansion material with temperature-independent mechanical properties. To assess the feasibility of the proposed model, the bending moment versus curvature of the finite element solution is compared with experimental results obtained in literature and good agreements are found between them. Detailed finite element results such as contact pressures, armour wire slip displacements and friction, normal and transverse bending stresses are also shown and compared with available analytical models. •Alternative three-dimensional finite element model describes the response of flexible pipes subject to combined axisymmetric and bending loads.•To simulate the response of a flexible pipe under axial tension or compression and uniform curvature, an equivalent thermal loading is employed.•The bending moment versus curvature of the finite element model is compared with experimental results obtained in literature.•Contact pressures, armour wire slips and friction, normal and transverse bending stresses are shown and results compared with analytical models.